De Novo Duplication of 11p15 Associated With Congenital Diaphragmatic Hernia - Gabriel C. Dworschak; Gabriel C. Dworschak; Hartmut Engels; Jessica Becker; Lukas Soellner; Thomas Eggermann; Florian Kipfmueller; Andreas Müller; Heiko Reutter; Heiko Reutter; Martina Kreiß (Frontiers Media S.A., 2018)
Background: Congenital diaphragmatic hernia (CDH) is a rare defect of the diaphragm commonly associated with high morbidity and mortality due to lung hypoplasia and pulmonary hypertension. Although in 70% of patients the etiology of a CDH remains unknown, a multitude of causative chromosomal aberrations has been identified.Case presentation: We describe the first case of isolated 11p15 duplication with CDH. The 18.6 Mb large duplication affected 285 RefSeq genes and included the Beckwith-Wiedemann (BWS)-associated imprinting control region 2 (ICR2, KCNQ1OT1 TSS DMR), whereas the ICR1 (H19 TSS DMR) was not affected. We were able to demonstrate de novo occurrence of the duplication. The paternal origin of the chromosomal material was detected by methylation testing the ICR2. Corresponding to other patients with duplications of the paternal ICR2 copy, a BWS phenotype is not present.Conclusions: The patient presented here together with the review of four other cases from the literature indicate an association between duplications of the chromosomal region 11p15 and developmental defects of the diaphragm. Thus, we suggest duplications of 11p15 as a rare cause of CDH. This association may or may not appear in the context of BWS depending on the extent of the duplication and the imprinting status. Hence, a genetic workup should be performed in patients with CDH, particularly when other abnormalities are noted.